2016
DOI: 10.1371/journal.pone.0156053
|View full text |Cite
|
Sign up to set email alerts
|

Lung-Derived Microscaffolds Facilitate Diabetes Reversal after Mouse and Human Intraperitoneal Islet Transplantation

Abstract: There is a need to develop three-dimensional structures that mimic the natural islet tissue microenvironment. Endocrine micro-pancreata (EMPs) made up of acellular organ-derived micro-scaffolds seeded with human islets have been shown to express high levels of key beta-cell specific genes and secrete quantities of insulin per cell similar to freshly isolated human islets in a glucose-regulated manner for more than three months in vitro. The aim of this study was to investigate the capacity of EMPs to restore e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 58 publications
1
29
1
4
Order By: Relevance
“…This is supported by our in vitro (MTT, live/dead, and GSIS assays) and in vivo (metabolic analysis) data showing that bioscaffolds made from cryogel alone improved islet function and viability when compared to islets alone. Similar results showing improvement in islet function have been reported using bioscaffolds that have been either coated with ECM components43 or those using ECM derived from lung tissue 44,45. However, to minimize the effect of any ROS produced from our hydrophilic collagen‐based cryogel bioscaffold, we tested different concentrations of CPO and found that 0.25 wt% concentration of CPO produced the most desirable results; these bioscaffolds generated biologically relevant concentrations of oxygen17,27 over 21 d while also producing the lowest amount of ROS compared to bioscaffolds which incorporated higher concentrations of CPO.…”
Section: Discussionsupporting
confidence: 70%
“…This is supported by our in vitro (MTT, live/dead, and GSIS assays) and in vivo (metabolic analysis) data showing that bioscaffolds made from cryogel alone improved islet function and viability when compared to islets alone. Similar results showing improvement in islet function have been reported using bioscaffolds that have been either coated with ECM components43 or those using ECM derived from lung tissue 44,45. However, to minimize the effect of any ROS produced from our hydrophilic collagen‐based cryogel bioscaffold, we tested different concentrations of CPO and found that 0.25 wt% concentration of CPO produced the most desirable results; these bioscaffolds generated biologically relevant concentrations of oxygen17,27 over 21 d while also producing the lowest amount of ROS compared to bioscaffolds which incorporated higher concentrations of CPO.…”
Section: Discussionsupporting
confidence: 70%
“…[14][15][16] An ECM substitute such as biocompatible scaffolds and hydrogels can be used as a method of cellular delivery and support islet engraftment, survival, and angiogenesis in the subcutaneous site. [27][28][29][30][31] In particular, the native islet ECM and vasculature are removed during the islet isolation process subsequently impairing islet function and thereby necessitating their replacement immediately post-transplant.…”
Section: Introductionmentioning
confidence: 99%
“…При этом нарушается не только васкуляризация и иннервация островков, но и принципиально меняется сигнальное взаимодействие между островковыми клетками (ОК) и компонентами внеклеточного матрикса (ВКМ) [8][9][10], регулирующее множество аспектов физиологии островков, включая выживаемость, пролиферацию и секрецию инсулина. В качестве альтернативы трансплантации ОК предпринимаются немногочисленные попытки создания тканеинженерной конструкции поджелудочной железы (ТИК ПЖ) [11], состоящей из аллогенных ОЛ и биоактивного резорбируемого матрикса, создающего островкам микроокружение, сходное с нативным ВМК, и обеспечивающего ОЛ необходимые условия для выживаемости и функциональной активности [12][13][14][15].…”
Section: Introductionunclassified